Substance Use and Performance of Toxicology Screens in the Greater Cincinnati Northern Kentucky Stroke Study. Issue 10 (7th July 2022) - Madsen, Tracy E.; Cummings, Olivia W.; De Los Rios La Rosa, Felipe; Khoury, Jane C.; Alwell, Kathleen; Woo, Daniel; Ferioli, Simona; Martini, Sharyl; Adeoye, Opeolu; Khatri, Pooja; Flaherty, Matthew L.; Mackey, Jason; et al.
Abstract : Background: Though stroke risk factors such as substance use may vary with age, less is known about trends in substance use over time or about performance of toxicology screens in young adults with stroke. Methods: Using the Greater Cincinnati Northern Kentucky Stroke Study, a population-based study in a 5-county region comprising 1.3 million people, we reported the frequency of documented substance use (cocaine/marijuana/opiates/other) obtained from electronic medical record review, overall and by race/gender subgroups among physician-adjudicated stroke events (ischemic and hemorrhagic) in adults 20 to 54 years of age. Secondary analyses included heavy alcohol use and cigarette smoking. Data were reported for 5 one-year periods spanning 22 years (1993/1994–2015), and trends over time were tested. For 2015, to evaluate factors associated with performance of toxicology screens, multiple logistic regression was performed. Results: Overall, 2152 strokes were included: 74.5% were ischemic, mean age was 45.7±7.6, 50.0% were women, and 35.9% were Black. Substance use was documented in 4.4%, 10.4%, 19.2%, 24.0%, and 28.8% of cases in 1993/1994, 1999, 2005, 2010, and 2015, respectively ( P trend <0.001). Between 1993/1994 and 2015, documented substance use increased in all demographic subgroups. Adjusting for gender, comorbidities, and National Institutes of Health Stroke Scale, predictors of toxicology screens included Black race (adjusted odds ratio, 1.58 [95% CI, 1.02–2.45]), younger age (adjusted odds ratio, 0.70 [95% CI, 0.53–0.91], per 10 years), current smoking (adjusted odds ratio, 1.62 [95% CI, 1.06–2.46]), and treatment at an academic hospital (adjusted odds ratio, 1.80 [95% CI, 1.14–2.84]). After adding chart-reported substance use to the model, only chart-reported substance abuse and age were significant. Conclusions: In a population-based study of young adults with stroke, documented substance use increased over time, and documentation of substance use was higher among Black compared with White individuals. Further work is needed to confirm race-based disparities and trends in substance use given the potential for bias in screening and documentation. Findings suggest a need for more standardized toxicology screening.